Genetic variability studies on yield attributing traits in Palmyrah (Borassus flabellifer L.): Implications for crop improvement - Pooja, A; R Swarna Priya, R; Rajasree, V; Manikanda Boopathi, N; Arumugam, P M; Raveendran, M (Plant Science Today, 2025)
Palmyrah is a dioecious palm, which is known for its resilience in arid and semi-arid environments. It is used to produce numerous edible and non-edible products. The association among yield-related traits and their pattern of influence are useful in evaluating and planning the selection criteria for desirable traits. The aim of this study was to examine the genetic variability and character association among the Palmyrah genotypes. A total of thirty accessions of Palmyrah were used for this study. Eleven traits contributing to growth and yield were recorded and analysed for genetic variability, correlation and path analysis. The number of bunches, single fruit weight and fruit yield per palm recorded the higher estimates of GCV and PCV. Among the eleven traits, 10 traits showed high heritability and GAM, whereas the trunk girth showed high heritability and moderate GAM. Fruit yield per palm exhibited positive correlation with trunk girth, number of bunches, number of fruits per bunch and single fruit yield. Path coefficient analysis revealed that the traits like number of bunches and single fruit weight had a positive and high direct effect on fruit yield per palm. Based on these results, Palmyrah improvement programme could be accelerated by selecting the variables that have a stronger correlation to fruit yield per palm and moderate to high estimates of PCV, GCV, heritability and high genetic advancement.